2020
DOI: 10.1111/1365-2656.13398
|View full text |Cite
|
Sign up to set email alerts
|

Legacy effects of fish but not elevation influence lake ecosystem response to environmental change

Abstract: How communities reorganize during climate change depends on the distribution of diversity within ecosystems and across landscapes. Understanding how environmental and evolutionary history constrain community resilience is critical to predicting shifts in future ecosystem function. The goal of our study was to understand how communities with different histories respond to environmental change with regard to shifts in elevation (temperature, nutrients) and introduced predators. We hypothesized that community res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…Prior experiments from the region demonstrated intraspecific differences in adaptive constitutive and plastic anti‐predator traits in zooplankton from several lakes with fish, relative to trout‐naive zooplankton (Fisk et al 2007, Latta et al 2007). Another recent mesocosm experiment from our study region tested the response of trout‐experienced versus trout‐naive zooplankton to fish predation and shifts in elevation (Symons et al 2020). In contrast to our design, Symons et al (2020) used a combined inoculum of zooplankton from three lakes for each treatment condition and found that the effects of prior exposure to trout far exceeded those of elevation of origin on zooplankton community biomass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior experiments from the region demonstrated intraspecific differences in adaptive constitutive and plastic anti‐predator traits in zooplankton from several lakes with fish, relative to trout‐naive zooplankton (Fisk et al 2007, Latta et al 2007). Another recent mesocosm experiment from our study region tested the response of trout‐experienced versus trout‐naive zooplankton to fish predation and shifts in elevation (Symons et al 2020). In contrast to our design, Symons et al (2020) used a combined inoculum of zooplankton from three lakes for each treatment condition and found that the effects of prior exposure to trout far exceeded those of elevation of origin on zooplankton community biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent mesocosm experiment from our study region tested the response of trout‐experienced versus trout‐naive zooplankton to fish predation and shifts in elevation (Symons et al 2020). In contrast to our design, Symons et al (2020) used a combined inoculum of zooplankton from three lakes for each treatment condition and found that the effects of prior exposure to trout far exceeded those of elevation of origin on zooplankton community biomass. Together these results support our contention that thousands of generations of zooplankton exposure to trout predators is a significant source of variation between our two zooplankton communities.…”
Section: Discussionmentioning
confidence: 99%